Development of bioabsorbable polylactide membrane with controllable hydrophilicity for adjustment of cell behaviours. Issue 1 (17th January 2018) - Yang, Yang; Qiu, Xiaofeng; Sun, Yi; Wang, Yifeng; Wang, Jine; Li, Yulin; Liu, Changsheng
Abstract : Cell functions can be mediated through their interactions with the microenvironments, which highly depend on the surface state of the substrate. However, how to finely adjust the surface of biomaterials is still very challenging. In this study, poly(d, l -lactide) (PDLLA) with high molecular weight was synthesized via ring opening polymerization, which was hot-pressed into PDLLA membrane. In order to modify the hydrophobicity of the membrane (a limiting factor for its biomedical application), an amphiphilic monomethoxyl poly(ethylene glycol)-b-poly(d, l -lactide) (PEG-PDLLA) was selected to improve its surface hydrophilicity through a simple self-assembly approach. It was found that the contact angles of the modified membrane can be well controlled by variation of PEG-PDLLA concentrations. In vitro cell biological study indicates that optimized cell adhesion can be achieved on the modified membrane with a contact angle of around 50° via its self-assembly with an ethanol/water solution of PEG-PDLA (35 mg ml −1 ). The surface modification of the membrane also changed its biodegradation property in the process of its incubation period up to 240 days. The surface modification method may afford an effective way for adjustment of the surface (interface) of membrane (scaffolds) of different biomaterials, beyond polylactide.